Immunization with an autotransporter protein of Orientia tsutsugamushi provides protective immunity against scrub typhus. - Na-Young Ha; Prashant Sharma; Gwanghun Kim; Yuri Kim; Chan-Ki Min; Myung-Sik Choi; Ik-Sang Kim; Nam-Hyuk Cho (Public Library of Science (PLoS), 2015)
BACKGROUND:Scrub typhus is an acute febrile disease caused by Orientia tsutsugamushi infection. Recently, the rapid increase of scrub typhus incidence in several countries within the endemic region has become a serious public health issue. Despite the wide range of preventative approaches that have been attempted in the past 70 years, all have failed to develop an effective prophylactic vaccine. Currently, the selection of the proper antigens is one of the critical barriers to generating cross-protective immunity against antigenically-variable strains of O. tsutsugamushi. METHODOLOGY/PRINCIPAL FINDINGS:We examined the potential role of ScaA protein, an autotransporter protein of O. tsutsugamushi, in bacterial pathogenesis and evaluated the protective attributes of ScaA immunization in lethal O. tsutsugamushi infection in mice. Our findings demonstrate that ScaA functions as a bacterial adhesion factor, and anti-ScaA antibody significantly neutralizes bacterial infection of host cells. In addition, immunization with ScaA not only provides protective immunity against lethal challenges with the homologous strain, but also confers significant protection against heterologous strains when combined with TSA56, a major outer membrane protein of O. tsutsugamushi. CONCLUSIONS/SIGNIFICANCE:Immunization of ScaA proteins provides protective immunity in mice when challenged with the homologous strain and significantly enhanced protective immunity against infection with heterologous strains. To our knowledge, this is the most promising result of scrub typhus vaccination trials against infection of heterologous strains in mouse models thus far.